Mapping Shariah Supervisory Board Literature for Islamic Finance Development - Yusril; Rusanti, Ega; Zulaikha, Siti (Universitas Airlangga, 2024)
This study aims to map the intellectual structure of research regarding the role of the Sharia Supervisory Board (SSB) in the development of Islamic finance. This mapping includes bibliographic analysis, keywords, and a network map of research trends. This study uses the bibliometric method by utilizing the Biblioshiny and Vos Viewer analysis tools. The researcher used 315 articles published on the Scopus page from 1988–2023. The results show that in the last 10 years, a topic about SSB has received great attention from researchers with an increase in article production. This topic has been discussed by authors from Indonesia, Malaysia, and Bangladesh. The results of the study also show that there are five clusters consisting of the role of SSB in the implementation of shariah governance; the role of SSB in encouraging the development of Islamic finance; SSB in improving the performance of Islamic banking; the characteristics of SSB; and the leadership and political system. The results of this study guide researchers, practitioners, and policymakers to understand the direction and focus of the Sharia Advisory Council (SSB) research. Its practical implications include strengthening the conceptual foundation of the SSB, supporting the development of the Islamic finance industry, and potentially becoming the basis for the development of a new conceptual framework in the future.